Dampak Insentif Fiskal Perpajakan Terhadap Usaha Mikro, Kecil, Dan Menengah (UMKM) - Rizka Handayani Pohan; Gustira Sabrina Irawan; Rima Vania Ramadhani; Farahdinny Siswajhanty; Balqis Dwi Amanda Putri (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Taxes are often a key factor that influences the growth and desirability of MSME businesses. A fair and equitable tax policy can encourage the growth of MSMEs by creating an environment that supports investment and business development. However, MSMEs face challenges related to tax policy, including: The complexity of tax laws and regulations, high administrative costs, and lack of access to information and technical support related to taxation. Therefore, recommendations are given to the government to comply with tax regulations, provide greater tax relief to MSMEs, and increase access to tax information and support. This study makes an important contribution to understanding the relationship between tax policy and MSMEs and provides a basis for developing more effective policies to support the growth and subscription of MSME businesses